Novel Mechanisms Modulating Palmitate-Induced Inflammatory Factors in Hypertrophied 3T3-L1 Adipocytes by AMPK - Naru Morita; Toshio Hosaka; Atsuko Kitahara; Toshitaka Murashima; Hirohisa Onuma; Yoshikazu Sumitani; Kazuto Takahashi; Toshiaki Tanaka; Takuma Kondo; Hitoshi Ishida (Journal of Diabetes Research)
Objective. A growing body of evidence indicates that AMP-activated protein kinase (AMPK) contributes to not only energy metabolic homeostasis but also the inhibition of inflammatory responses. However, the underlying mechanisms remain unclear. To elucidate the role of AMPK, in this study, we observed the effects of AMPK activation on monocyte chemoattractant protein-1 (MCP-1) release in mature 3T3-L1 adipocytes. Methods. We observed signal transduction pathways regulating MCP-1, which increased in obese adipocytes, in an in vitro model of hypertrophied 3T3-L1 adipocytes preloaded with palmitate. Results. Palmitate-preloaded cells exhibited significant increase in MCP-1 release and triglyceride (TG) deposition. Increased MCP-1 release and TG deposition were significantly decreased by an AMPK activator. In addition, the AMPK activator not only markedly diminished MCP-1 secretion but also augmented phosphorylation of nuclear factor-κB (NF-κB) and extracellular signal-regulated kinase (ERK) 1/2. In contrast, MCP-1 release suppression was abolished by the AMPK inhibitor compound C and the MEK inhibitor U0126. Conclusions. MCP-1 release from hypertrophied adipocytes is suppressed by AMPK activation through the NF-κB and ERK pathways. These findings provide evidence that AMPK plays a crucial role in ameliorating obesity-induced inflammation.